Digital Health Inclusion: A Pilot Study of Health Services Deployment Using Communications Satellite for the Underserved in Nigeria - Lawal, Lasisi Salami; Alale, Abimobola; Iheanacho, Theddeus; Ibrahim, Isa Ali; Udoyen, Ubong; Jafaar, Abdulrahman; Davey, Gail; Chatwin, Chris Radwin; Aibinu, Abiodun Musa; Sambo, Mohammed Nasir (British Journal of Healthcare and Medical Research, 2023)
Health service delivery in Nigeria is constrained by: brain drain, insufficient infrastructure and technology, poor and inadequate medical facilities and paucity of medical specialists in rural and remote regions - thus leading to a high rate of “medical tourism”. With increasing mobile phone ownership in Nigeria, mobile technology-based telemedicine has the potential to improve Nigeria’s healthcare delivery with enabling infrastructural facilities. In this paper, a pilot study that uses Nigeria’s communication satellite system for virtual Telemedicine connection between health practitioners and underserved communities using the “one2one” mobile telemedicine application is reported. This pilot study aimed to deploy Nigeria’s communication satellite system to enable virtual telemedicine connection between health practitioners and underserved communities using the “one2one” mobile telemedicine app. Successful deployment of a 1.8m VSAT dish at the pilot clinic and testing showed robust internet connectivity with a time delay of 250ms per hop. Furthermore, the One2one app was successfully installed on health practitioners’ tablets/phone and patients’ phone/tablets. Over 100 patients were treated using the one2one app connected through the satellite internet. The one2one app was highly rated by patients and healthcare providers in terms of usability with the highest score being ease of use 87%. This study shows that Nigeria’s communications satellite can be deployed to support mobile telemedicine as part of the effort to increase access to doctors and specialists in medically underserved areas of Nigeria.